Comorbid Medical Conditions in Vascular Dementia: A Matched Case–Control Study. Issue 8 (August 2015) - Habeych, Miguel E.; Castilla-Puentes, Ruby
Abstract : Abstract: The objective of the study was to compare the presence of comorbid medical conditions between patients with a vascular dementia (VaD) and a control group, from the Integrated Healthcare Information Services (IHCIS) database. VaD was defined by the International Classification of Diseases, 9th Revision, Clinical Modification ( ICD-9-CM ) codes 290.40, 290.4, 290.41, 290.42, and, 290.43. An individual matching method was used to select the controls, which were matched to cases on a 15:1 ratio by age, gender, type of health plan, and pharmacy benefits. Alzheimer's disease, any other dementia or cognitive deficits associated were considered exclusion criteria. Among the IHCIS patients 60 years of age or older and full year of eligibility during 2010, there were 898 VaD patients, from which 63.6% were women. Concurrent presence of cerebrovascular disease, atherosclerosis, heart failure, and atrial fibrillation were found at 12.6, 4.6, 2.8, and 1.7 times higher in VaD patients, respectively. Compared to controls, VaD patients had more septicemia, injuries, lung diseases including chronic obstructive pulmonary disease, and urinary diseases (all with df = 897, 1; p < 0.0001). The present study confirms that these four medical comorbidities are frequent complications of VaD and physicians should be alert to the presence of them in patients with VaD.